A simple extension of the commonly used fitting equation for oscillatory structural forces in case of silica nanoparticle suspensions - Schön, Sebastian; von Klitzing, Regine (Beilstein Journal of Nanotechnology, 2018)
Background: The ordering of molecules or particles in the vicinity of a confining surface leads to the formation of an interfacial region with layers of decreasing order normal to the confining surfaces. The overlap of two interfacial regions gives rise to the well-known phenomenon of oscillatory structural forces. These forces are commonly fitted with an exponentially decaying harmonic oscillation as introduced by Israelachvili (Israelachvili, J. N. Intermolecular & surface forces; Academic Press: San Diego, CA, USA, 1985). From the fit three important parameters are obtained, namely wavelength, amplitude and decay length, which are related to the period, the strength and the correlation length of the oscillatory structural forces, respectively. The paper addresses structural forces between a silica microsphere and a silicon wafer across silica nanoparticle suspensions measured with a colloidal probe AFM. Using the simple fitting procedure with three parameters often leads to underestimation of actually measured forces. The deviation of the fit from the experimental data is especially pronounced at small distances of the confining surfaces and at high concentrations of silica nanoparticles. As a consequence, the parameters of the common fit equation vary with the starting point of the fit. Although the wavelength is least affected and seems to be quite robust against the starting point of the fit, all three parameters show distinct oscillations, with a period similar to the wavelength of the oscillatory structural forces themselves. The oscillations of amplitude and decay length, which are of much higher magnitude, show a phase shift of 180° implying not only a dependence on the starting point of the fit but also on each other. The range affected by this systematic deviation of the fit parameters is much larger than the optically perceived mismatch between fit and experimental data, giving a false impression of robustness of the fit.Results: By introducing an additional term of exponentially decaying nature the data can be fitted accurately down to very small separations and even for high silica nanoparticle concentrations (10 wt %). Furthermore wavelength, amplitude and decay length become independent of the starting point of the fit and in case of the latter two of each other. The larger forces at small separations indicate a more pronounced ordering behavior of the particles in the final two layers before the wall. This behavior is described by the proposed extension of the common fit equation.Conclusion: Thus, the extension increases the accessible data range in terms of separation and concentration and strongly increases the accuracy for all fitting parameters in the system studied here.
Keywords: confinement; depletion; fitting; silica nanoparticles; structural forces

(untitled) - Horn, R. G.; Israelachvili, J. N. (J. Chem. Phys., 1981)

(untitled) - Israelachvili, J. N.; Pashley, R. M. (Nature, 1983)

(untitled) - Christov, N. C.; Danov, K. D.; Zeng, Y.; Kralchevsky, P. A.; von Klitzing, R. (Langmuir, 2010)

(untitled) - Richetti, P.; Kékicheff, P. (Phys. Rev. Lett., 1992)

(untitled) - Ducker, W. A.; Xu, Z.; Clarke, D. R.; Israelachvili, J. N. (J. Am. Ceram. Soc., 1994)

(untitled) - Smith, A. M.; Lovelock, K. R. J.; Gosvami, N. N.; Welton, T.; Perkin, S. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Nikolov, A. D.; Wasan, D. T. (J. Colloid Interface Sci., 1989)

(untitled) - Kralchevsky, P. A.; Nikolov, A. D.; Wasan, D. T.; Ivanov, I. B. (Langmuir, 1990)

(untitled) - Nikolov, A. D.; Wasan, D. T. (Langmuir, 1992)

(untitled) - Bergeron, V.; Radke, C. J. (Langmuir, 1992)

(untitled) - Kralchevsky, P. A.; Danov, K. D.; Anachkov, S. E. (Curr. Opin. Colloid Interface Sci., 2015)

(untitled) - Sharma, A.; Walz, J. Y. (J. Chem. Soc., Faraday Trans., 1996)

(untitled) - Sharma, A.; Tan, S. N.; Walz, J. Y. (J. Colloid Interface Sci., 1997)

(untitled) - Wasan, D. T.; Nikolov, A. D. (Nature, 2003)

(untitled) - Wasan, D.; Nikolov, A.; Kondiparty, K. (Curr. Opin. Colloid Interface Sci., 2011)

(untitled) - Nikolov, A.; Wasan, D. (Adv. Colloid Interface Sci., 2014)

(untitled) - Kegler, K.; Salomo, M.; Kremer, F. (Phys. Rev. Lett., 2007)

(untitled) - Piech, M.; Walz, J. Y. (J. Phys. Chem. B, 2004)

(untitled) - Tulpar, A.; Van Tassel, P. R.; Walz, J. Y. (Langmuir, 2006)

(untitled) - Drehlich, J.; Long, J.; Xu, Z.; Masliyah, J.; Nalaskowski, J.; Beauchamp, R.; Liu, Y. (J. Colloid Interface Sci., 2006)

(untitled) - James, G. K.; Walz, J. Y. (J. Colloid Interface Sci., 2014)

(untitled) - Horn, R. G.; Israelachvili, J. N.; Perez, E. (J. Phys. (Paris), 1981)

Thin liquid films - Ivanov, I. B.; Dimitrov, D. S. (Marcel Dekker, Inc., 1988)

(untitled) - Stubenrauch, C.; von Klitzing, R. (J. Phys.: Condens. Matter, 2003)

(untitled) - von Klitzing, R.; Kolarić, B.; Jaeger, W.; Brandt, A. (Phys. Chem. Chem. Phys., 2002)

Polyelectrolytes with defined molecular architecture I - von Klitzing, R.; Tieke, B. (Polyelectrolyte Membranes, 2004)

(untitled) - McNamee, C. E.; Tsujii, Y.; Ohshima, H.; Matsumoto, M. (Langmuir, 2004)

(untitled) - Qu, D.; Pedersen, J. S.; Garnier, S.; Laschewsky, A.; Möhwald, H.; von Klitzing, R. (Macromolecules, 2006)

(untitled) - Üzüm, C.; Christau, S.; von Klitzing, R. (Macromolecules, 2011)

(untitled) - Piech, M.; Walz, J. Y. (J. Colloid Interface Sci., 2002)

(untitled) - Jönsson, B.; Broukhno, A.; Forsman, J.; Åkesson, T. (Langmuir, 2003)

(untitled) - Kittner, M.; Klapp, S. H. L. (J. Chem. Phys., 2007)

(untitled) - Jordanovic, J.; Klapp, S. H. L. (Phys. Rev. Lett., 2008)

(untitled) - Klapp, S. H. L.; Zeng, Y.; Qu, D.; von Klitzing, R. (Phys. Rev. Lett., 2008)

(untitled) - Zeng, Y.; von Klitzing, R. (J. Phys.: Condens. Matter, 2012)

(untitled) - Zeng, Y.; Grandner, S.; Oliveira, C. L. P.; Thünemann, A. F.; Paris, O.; Pedersen, J. S.; Klapp, S. H. L.; von Klitzing, R. (Soft Matter, 2011)

(untitled) - Zeng, Y.; von Klitzing, R. (Soft Matter, 2011)

(untitled) - Grandner, S.; Zeng, Y.; von Klitzing, R.; Klapp, S. H. L. (J. Chem. Phys., 2009)

(untitled) - Zeng, Y.; von Klitzing, R. (Langmuir, 2012)

(untitled) - Chu, X. L.; Nikolov, A. D.; Wasan, D. T. (Langmuir, 1994)

(untitled) - Chu, X. L.; Nikolov, A. D.; Wasan, D. T. (J. Chem. Phys., 1995)

(untitled) - Trokhymchuk, A.; Henderson, D.; Nikolov, A.; Wasan, D. T. (J. Phys. Chem. B, 2003)

(untitled) - Henderson, D. (J. Colloid Interface Sci., 1988)

(untitled) - Kjellander, R.; Sarman, S. (Chem. Phys. Lett., 1988)

(untitled) - Attard, P.; Parker, J. L. (J. Phys. Chem., 1992)

(untitled) - Pollard, M. L.; Radke, C. J. (J. Chem. Phys., 1994)

(untitled) - Evans, R.; Henderson, J. R.; Hoyle, D. C.; Parry, A. O.; Sabeur, Z. A. (Mol. Phys., 1993)

(untitled) - Trokhymchuk, A.; Henderson, D.; Wasan, D. T. (J. Colloid Interface Sci., 1999)

(untitled) - Roth, R.; Evans, R.; Dietrich, S. (Phys. Rev. E, 2000)

(untitled) - Henderson, D.; Wasan, D. T.; Trokhymchuk, A. (Condens. Matter Phys., 2001)

Intermolecular & surface forces - Israelachvili, J. N. (Academic Press, 1985)

(untitled) - Kralchevsky, P. A.; Denkov, N. D. (Chem. Phys. Lett., 1995)

(untitled) - Trokhymchuk, A.; Henderson, D.; Nikolov, A.; Wasan, D. T. (Langmuir, 2001)

(untitled) - Evans, R.; Leote de Carvalho, R. J. F.; Henderson, J. R.; Hoyle, D. C. (J. Chem. Phys., 1994)

(untitled) - Moazzami-Gudarzi, M.; Kremer, T.; Valmacco, V.; Maroni, P.; Borkovec, M.; Trefalt, G. (Phys. Rev. Lett., 2016)

(untitled) - Moazzami-Gudarzi, M.; Maroni, P.; Borkovec, M.; Trefalt, G. (Soft Matter, 2017)

(untitled) - Smith, A. M.; Lee, A. A.; Perkin, S. (Phys. Rev. Lett., 2017)

(untitled) - Coles, S. W.; Smith, A. M.; Fedorov, M. V.; Hausen, F.; Perkin, S. (Faraday Discuss., 2018)

(untitled) - Kern, W. (Semicond. Int., 1984)

(untitled) - Ducker, W. A.; Senden, T. J.; Pashley, R. M. (Nature, 1991)

(untitled) - Butt, H.-J. (Biophys. J., 1991)

(untitled) - Walters, D. A.; Cleveland, J. P.; Thomson, N. H.; Hansma, P. K.; Wendman, M. A.; Gurley, G.; Elings, V. (Rev. Sci. Instrum., 1996)

(untitled) - Derjaguin, B. (Kolloid-Z., 1934)